Persepsi Masyarakat terhadap Faktor-Faktor Penyebab Banjir di Perumahan Total Persada Raya Kota Tangerang - Yutantri, Visca; Suryandari, Ratnawati Yuni; Putri, Mega Novetrishka; Widyawati, Laili Fuji (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
Flood disaster is a disaster that often occurs in Indonesia, especially during the rainy season. One of the areas in Indonesia that experiences flooding every year is Tangerang City. The Total Persada Raya housing estate, located in Gembor Village, is one of the points most frequently flooded. The negative impact of this flood was not only experienced by the housing community, but also felt by people outside the housing area because the floods that occurred overflowed to Jalan Total Persada Raya where the road is the connecting access between Tangerang City and Tangerang Regency. Disaster management such as raising river embankments has been carried out, but reality floods still occur. Therefore, this study aims to determine the characteristics of flooding, the factors, and the dominant factors causing flooding in Total Persada Raya Housing based on public perception. The analytical method used in this research is descriptive quantitative method and multiple linear regression analysis to connect the factors that influence each other and determine the dominant factor. The results showed that the flood disaster in Total Persada Raya Housing was a regular flood, with the influencing factors, namely natural factors such as rainfall (with a regression coefficient value of 0.941), and physiography (0.017), as well as non-natural factors such as land use (0.282), infrastructure conditions (0.916) and human activities (1.072); with human activities as the dominant factor that causes a flood. The implication of this research is that if humans maintain and protect nature, then nature will take care of humans.